The role of the clinical research nurse in the context of clinical trials: a mini-review - Pais, Daniela; Amado, Tiago; Monteiro, Pedro; Santos, Cláudio (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Elucidate the role of clinical research nurses in the development of clinical trials. Methods: This study employs a theoretical-reflexive methodology, drawing upon an approach derived from the analysis of international publications. The study is structured by the researchers and informed by their experience gained through collaboration on multiple networks. Results and discussion: A clinical research nurse is a professional whose contributions and responsibilities ensure the quality of clinical research from inception to completion. They are involved in a number of key areas, including the evaluation and feasibility of research proposals, the negotiation of financial agreements, the implementation of trials, the supervision of trial sites, the conduct of clinical trials that involves patient recruitment, follow-up and education, informed consent process, data collection and product administration, and the management of participant expenses. Conclusions: The involvement of nurses in research teams facilitates a more efficacious approach to patient care. Despite the fact that the role of the clinical research nurse is present and recognised in multidisciplinary teams in clinical trials, the exact nature of the role remains unclear. It is of great importance to construct and promote the research nursing specialty.